2015
DOI: 10.1553/giscience2015s434
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Monitoring of the Environmental Impact of a Refugee Camp Based on Landsat Time Series: The Example of Deforestation and Reforestation During the whole Lifespan of the Camp Lukole, Tanzania

Abstract: This study deals with the long-term monitoring of the environmental impact of the refugee camp Lukole, Tanzania. Based on high resolution (HR) satellite time series of different Landsat sensors, the whole lifespan of the camp is covered, starting before the camp was established (1994) until seven years after the dismantling (2015). A fully automated preclassification approach for different Landsat sensors was applied, and the results were integrated into a post-classification object-specific change comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…They make up about 630 hectares, which correlates well with the 572 hectares of forest decrease reported by Labib et al [35], who estimated the conversion A different form of change visualization is presented in Figure 7. This approach was originally suggested by Langer [116,117], who investigated landscape changes around the Lukole refugee camp in Tanzania based on a time-series of 42 Landsat images. For this study, squares of the size of 300 m width and height were generated, and the dominant landcover was assessed for each square and date on the basis of the determination of each square's mode.…”
Section: Land Cover Changementioning
confidence: 99%
“…They make up about 630 hectares, which correlates well with the 572 hectares of forest decrease reported by Labib et al [35], who estimated the conversion A different form of change visualization is presented in Figure 7. This approach was originally suggested by Langer [116,117], who investigated landscape changes around the Lukole refugee camp in Tanzania based on a time-series of 42 Landsat images. For this study, squares of the size of 300 m width and height were generated, and the dominant landcover was assessed for each square and date on the basis of the determination of each square's mode.…”
Section: Land Cover Changementioning
confidence: 99%
“…Their research found that increasing IDP camps caused a considerable decrease in woody vegetation surrounding the camp area. Langer et al (2015) [34] monitored the long-term environmental impacts, including deforestation, of refugee camps using Landsat data in Lukole, Tanzania. The authors observed that the development of camps caused significant degradation of the natural vegetation surrounding the camps area.…”
Section: Introductionmentioning
confidence: 99%
“…Algae, invertebrates, and fish in the Slovenia's Isonzo River, for example, still contain elevated mercury levels from munitions discharged nearby during World War I, and large swathes of mangrove forests defoliated during the Vietnam War have never recovered . Some postwar biodiversity impacts represent a straightforward continuation of effects begun during wartime, such as persistent deforestation near long‐term refugee camps, but others play out more subtly. The previously mentioned reduction in North Sea fisheries during World War II, for example, altered the abundance of various age classes for multiple fish species in a way that affected population dynamics for decades afterward .…”
Section: Postwar Activitiesmentioning
confidence: 99%
“…152,153 r Persistent deforestation and elevated hunting levels near long-term camps for refugees and internally displaced populations. 151 r Persistent increase in hunting from proliferation of small arms. 139 r Lasting ecological effects from wartime impacts to wildlife populations and habitats.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation